Balancing on carbon storage and ecological security in urban areas: The case of Dongguan city, China - Xinyi Wang; Fenzhen Su; Fengqin Yan; Vincent Lyne; Yikun Cui; Bin He; Rong Fan (Sustainable Futures)
Land-use changes from rapid coastal urban expansion fragments ecosystems and reduces carbon storage. Current and future national urban policies must therefore enhance carbon sink functions of ecosystems while maintaining spatial ecological structure networks. Here, we assessed current policies against future scenarios using systems thinking and land-use change simulation coupled to carbon-storage accounting. Three future scenarios for Dongguan City across ecological Natural Evolution Scenario, economic Economic Priority Scenario and balanced Harmonious Development Scenario show latter partly controls carbon loss through more robust ecological networks. However, by 2030, all scenarios show construction land expanding sharply across cultivated land and grassland, and carbon storage declines. Future urban expansion therefore seriously challenges effectiveness of current spatial policies which must be enhanced for future low carbon urban developments and protection of associated ecosystem connectivities. This study analyzed the maintenance of habitat connectivity and carbon storage under different development policies during urbanization and discussed the significance of policies in maintaining the stability of urban ecological networks. With this effort, a new perspective on the maintenance of ecological security patterns is provided, serving as a fundamental reference for future urban planning decisions.